Welding Deformation of Hydraulic Support Measurements by Using FBG Sensors - Shangyu Du; Guofa Wang; Yajun Xu; Ying Ma; Desheng Zhang; Qiang Ma; Xingtong Yue (Advances in Civil Engineering)
The welding deformation and cracking of hydraulic support have always been an important issue that impacts product quality and performance in the industry. In order to quantify the deformation of the welding seam of the reverse four-bar linkage hydraulic support under loading conditions, a real-time weld monitoring system based on sensitive fiber Bragg grating sensors is designed. The strength test and the cycle life test of the top coal caving reverse four-link support with four typical eccentric loads were conducted, respectively. The strength test results prove that the fiber Bragg grating sensor is accurate enough to measure welding deformation of hydraulic support; the measurement resolution reaches 0.1 μm. The eccentric load experiment produces the reverse four-bar torsion, especially when the top beam is at a low position; the maximum deformation of the weld is 100 μm. In the cycle test, a phenomenon has been captured, i.e., the welds present a baseline shift along with the cyclic load and even jump. It indicates that the hydraulic support changes from one stable state to another stable state. This work not only provides a feasible solution for welding deformation monitoring but also provides a possibility for the whole life cycle monitoring of hydraulic supports.